FTO ameliorates doxorubicin-induced cardiotoxicity by inhibiting ferroptosis via P53–P21/Nrf2 activation in a HuR-dependent m6A manner - Yang, Yunfan; Ren, Jiajun; Zhang, Jifeng; Shi, Henghe; Wang, Junnan; Yan, Youyou (Redox biology, 2024)
Doxorubicin (DOX)-induced cardiotoxicity seriously limits its clinical applicability, and no therapeutic interventions are available. Ferroptosis, an iron-dependent regulated cell death characterised by lipid peroxidation, plays a pivotal role in DOX-induced cardiotoxicity. N6-methyladenosine (m6A) methylation is the most frequent type of RNA modification and involved in DOX-induced ferroptosis, however, its underlying mechanism remains unclear. P21 was recently found to inhibit ferroptosis by interacting with Nrf2 and is regulated in a P53-dependent or independent manner, such as through m6A modification. In the present study, we investigated the mechanism underlying m6A modification in DOX-induced ferroptosis by focusing on P21. Our results show that fat mass and obesity–associated protein (FTO) down-regulation was associated with DOX-induced cardiotoxicity. FTO over-expression significantly improved cardiac function and cell viability in DOX-treated mouse hearts and H9C2 cells. FTO over-expression significantly inhibited DOX-induced ferroptosis, and the Fer-1 inhibition of ferroptosis significantly reduced DOX-induced cardiotoxicity. P21 was significantly upregulated by FTO and activated Nrf2, playing a crucial role in the anti-ferroptotic effect. FTO upregulated P21/Nrf2 in a P53-dependent manner by mediating the demethylation of P53 or in a P53-independent manner by mediating P21/Nrf2 directly. Human antigen R (HuR) is crucial for FTO-mediated regulation of ferroptosis and P53–P21/Nrf2. Notably, we also found that P21 inhibition in turn inhibited HuR and P53 expression, while HuR inhibition further inhibited FTO expression. RNA immunoprecipitation assay showed that HuR binds to the transcripts of FTO and itself. Collectively, FTO inhibited DOX-induced ferroptosis via P21/Nrf2 activation by mediating the m6A demethylation of P53 or P21/Nrf2 in a HuR-dependent manner and constituted a positive feedback loop with HuR and P53–P21. Our findings provide novel insight into key functional mechanisms associated with DOX-induced cardiotoxicity and elucidate a possible therapeutic approach.